CTIM-11. PHASE 2 STUDY OF SL-701, A NOVEL IMMUNOTHERAPY, IN ADULTS WITH RECURRENT GBM: A HIGH PARAMETER FLOW CYTOMETRY ANALYSIS OF CD8+ T CELLS AND POTENTIAL IMPLICATIONS FOR PATIENT ENRICHMENT STRATEGIES. (12th November 2021) - Peereboom, David; Lindsay, Ross; Badruddoja, Michael; Nabors, L Burt; Kumthekar, Priya; Lieberman, Frank; Tran, David; Phuphanich, Surasak; Schiff, David; Sherman, Jonathan; Butowski, Nicholas; Dunbar, Erin; et al.
Abstract: Treatment of glioblastoma (GBM) remains a critical challenge and unmet medical need due to limited treatment options. SL-701 is a novel immunotherapy comprised of synthetic peptides designed to elicit a target-specific anti-tumor immune response against the GBM antigens IL-13Rα2, ephrinA2, and survivin. A multicenter, 2-stage, phase 2 clinical trial (NCT02078648) that evaluated the safety and efficacy of SL-701 in 74 adults with recurrent GBM was previously reported. This report describes preliminary data to suggest a correlation of immunocompetence to clinical outcome. In stage 2 (SL-701 + bevacizumab + poly-ICLC) the overall survival at 12 months was 50%. Two of 28 patients enrolled in stage 2 achieved CR (duration of response: 7.8 and 8.8 months) and 2 achieved PR (duration of response: 7.9 and 8.8 months). In a preliminary analysis to assess CD8+ T-cell responses, long-term survivors were comprised largely of subjects with an SL-701-induced target-specific CD8+ T-cell response, indicating a potential correlation of immunocompetence to clinical outcome. By week 24, SL-701-induced target-specific CD8+ T cells expressing IFNg were detected in 8 of 27 patients (30%) who had sufficient samples, with co-expression of PD-1, TIM3, and LAG3 detected in 4 patients. To further understand the T-cell response to SL-701, deep sequencing of target-specific CD8+ T cells using whole transcriptome-based molecular cytometry and high parameter (25+ color) flow cytometry is currently underway and updated data will be reported.